A turbine based domestic micro ORC system. (September 2017) - Klonowicz, Piotr; Witanowski, Łukasz; Jędrzejewski, Łukasz; Suchocki, Tomasz; Lampart, Piotr
Abstract: The paper presents an analysis of a turbine based micro ORC system for a domestic biomass boiler. The assumed nominal boiler capacity is in the range between 15 kW and 20 kW. Such a small thermal output is particularly difficult from the point of view of power generation. One of the major issues is the economic aspect of the system. In general, small systems are relatively more expensive. Another problem is poor electrical efficiency which results from the efficiencies of the individual components such as the expansion unit and the feed pump. Various working fluids are considered and also various methods of evaporation such as thermal oil loop, pressurized water loop and direct evaporation. The system efficiencies are examined. The main focused is laid on the turbine design. Due to low volume flow rates the rotational speeds must be high, even exceeding 100 krpm for some of the designs. Various turbine types are considered, however, the preferred choice is a partially admitted highly loaded impulse stage. Very small volume flow rates lead to blade channels that are difficult to manufacture, throats of the supersonic nozzles can be particularly problematic. Manufacturing difficulties impose worse tolerances which lead to bigger relative clearances and blade edge thicknesses which have a negative impact on the efficiency. High speed require appropriate bearing system which must be reliable and, particularly for such a small system, simple. Gas bearings (e.g. foil bearings) or ceramic bearings seem to fulfill these requirements.